The drowning house - Priest, Cherie (Poisoned Pen Press, 2024)
"A violent storm washes a mysterious house onto a rural Pacific Northwest beach, stopping the heart of the only woman who knows what it means. Her grandson, Simon Culpepper, vanishes in the aftermath, leaving two of his childhood friends to comb the small, isolated island for answers - but decades have passed since Melissa and Leo were close, if they were ever close at all. Now they'll have to put aside old rivalries and grudges if they want to find or save the man who brought them together in the first place - and on the way they'll learn a great deal about the sinister house on the beach, the man who built it, and the evil he's bringing back to Marrowstone Island"--